Some Issues of Identifying and Ensuring the "Best Interest of the Child" in RA - Petrosyan, Rubina (Bulletin of Yerevan University C: Jurisprudence, 2023)
The principle of ensuring the protection of the best interests of the child, embedded in international and domestic legal documents, underlies the legal system for child protection. It runs like a red thread in all legal acts regulating relations with the participation of a child; it also guides the competent authorities in almost all actions involving the child and, in the documents, drawn up as a result. The European Court of Human Rights, at the same time regarding the “best interests of the child” both as a substantive right, and as a principle, and as a norm of judicial procedure, thereby shows the comprehensive and fundamental significance of the latter. Therefore, in terms of identifying and reinforcing the evaluative concept of “the best interests of the child,” it is important to develop effective training in which the “best interests of the child” will be considered as the fundamental criterion in all matters affecting the child. As a result, in the event of competition between the interests of the child and the rights of others, in all cases, the supremacy of the interests of the child will be affirmed, and even an action determined by a judicial act cannot be carried out in a way that violates the best interests of the child.
Keywords: best interests of the child; legally protected interest; subjective right; guardianship and guardianship authority; the child's right to express an opinion; child's right to be heard; protection of rights